Penatalaksaan Holistik Wanita 67 Tahun di Puskesmas Rawat Inap Gedong Tataan Dengan Osteoarthritis Genu dan Hipertensi Grade II Melalui Pendekatan Kedokteran Keluarga - Deno Madasa Subing; Aila Karyus (Medula, 2020)
Osteoarthritis and hypertension are diseases often attack elderly. Incidence of hypertension based on blood pressure carried out in the population aged> 18 years in Indonesia is around 34.1%. Lampung Province is ranked 16th out of 33 provinces with the incidence of hypertension around 22%. The incidence of Osteoarthritis in women in Indonesia is 12.7%. This study analysis is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of study in a qualitative and quantitative manner.The 67-year-old Mrs. S, who has been diagnosed with Osteoarthritis and hypertension, has worries about her deteriorating health condition. Limitations of the patient's knowledge of the illness and bad lifestyle is a factor that causes problems that occur in patients and families.Holistic and comprehensive management of the patient's problems has been carried out by providing counseling to improve patient and family knowledge and providing a diet according to the patient's calorie needs.